Nexus between integrated reporting and firm value: a systematic literature review - Alatawi, Mohammed Saleem; Daud, Zaidi Mat; Johari, Jalila (Virtus Interpress, 2024)
The objective of this manuscript is to review the existing literature regarding integrated reporting (IR), focusing on theories, factors influencing it and its outcomes, and the methodologies adopted. The review encompasses a total of 27 studies conducted between 2006 and 2023. Following the earlier studies, four significant steps, i.e., searching for relevant studies, applying inclusion/exclusion criteria, applying methodological review protocol and finally synthetizing the protocol has been used to collect the relevant studies. The findings of the present study indicate that the majority of previous studies have relied on quantitative research methods and secondary data sources. Moreover, only two studies Boshnak (2022) and Alyousef and Alsughayer (2021) have considered both financial and non-financial disclosures which represent the features of IR. The findings of the present study also identified firm size, leverage, the degree of government ownership, the degree of family ownership, firm profitability, audit firm size, and firm age as the determinants of corporate social and environmental voluntary disclosure. Moreover, the finding also indicated that among all the theories that contribute to IR, only agency theory, resource-based theory, legitimacy theory and stakeholder theory were mostly considered by the previous studies.